Lesbian, Gay, Bisexual, Transgender/Gender Expansive, and Queer+ Volunteerism in the United States: Social Needs, Civic Engagement, and Psychosocial Well-being - Trevor G. Gates; Samantha Lillie; Callico Vargas (Journal of Psychosexual Health)
This viewpoint article explores how volunteerism and civic engagement are rapidly changing among lesbian, gay, bisexual, transgender/gender expansive, and queer+ (LGBTQ+) people who volunteer. The article provides commentary, a historical overview, a critical analysis of the literature, and an interpretation of the changing social mores toward LGBTQ+ people in the United States. We discuss the importance of engagement with the LGBTQ+ community as being crucial to identity development. LGBTQ+ volunteerism literature suggests that feeling connected to the LGBTQ+ community is the most important predictor of civic engagement and volunteering. References to existing literature are provided, along with recommendations for future research. In this article, we explore how to best engage LGBTQ+ volunteers, taking into account their cultural, linguistic, and other identities. We argue that voluntary organizations and communities should examine how they are meeting the needs of LGBTQ+ volunteers.